Insights into the allosteric regulation of Syk association with receptor ITAM, a multi-state equilibrium. Issue 8 (15th October 2015) - Feng, Chao; Post, Carol Beth
Abstract : Syk high-affinity association with receptor ITAM is regulated by a phosphorylation-dependent allosteric mechanism. NMR titration-curve/line-shape analyses determined phosphorylation increases the energetic barrier for, but does not prevent, isomerization. Abstract : The phosphorylation of interdomain A (IA), a linker region between tandem SH2 domains of Syk tyrosine kinase, regulates the binding affinity for association of Syk with doubly-phosphorylated ITAM regions of the B cell receptor. The mechanism of this allosteric regulation has been suggested to be a switch from the high-affinity bifunctional binding, mediated through both SH2 domains binding two phosphotyrosine residues of ITAM, to a substantially lower-affinity binding of only one SH2 domain. IA phosphorylation triggers the switch by inducing disorder in IA and weakening the SH2–SH2 interaction. The postulated switch to a single-SH2-domain binding mode is examined using NMR to monitor site-specific binding to each SH2 domain of Syk variants engineered to have IA regions that differ in conformational flexibility. The combined analysis of titration curves and NMR line-shapes provides sufficient information to determine the energetics of inter-molecular binding at each SH2 site along with an intra-molecular binding or isomerization step. A less favorable isomerization equilibrium associated with the changes in the SH2–SH2 conformational ensemble and IA flexibility accounts for the inhibition of Syk association with membrane ITAM regions when IA is phosphorylated, and refutes the proposed switch to single-SH2-domain binding. Syk localizes in the cell through its SH2 interactions, and this basis for allosteric regulation of ITAM association proposes for the first time a phosphorylation-dependent model to regulate Syk binding to alternate receptors and other signaling proteins that differ either in the number of residues separating ITAM phosphotyrosines or by having only one phosphotyrosine, a half ITAM.